Biocompatible Graphene for Bioanalytical Applications - Hu, Y (Springer, 2015)
This book highlights the latest advances in the use of graphene and bio-compatible-material-decorated graphene to detect various targets (e.g. DNA, RNA, amino acids, peptides, proteins, enzymes, antigens, glucose, DA, AA, UA, ATP, NADH, gas, ions, etc.). It focuses on the specific interaction of these substances with graphene (or modified graphene) and the efficient transduction of the target recognition event into detectable signals via various techniques. Particular emphasis is given to well-designed strategies for constructing graphene-based platforms and target determination. It also covers other bio-analytical applications including cellular imaging, drug delivery and bacteria inhibition, before turning to a discussion of future challenges and prospects of graphene in bio-analytical applications. This book is intended for researchers working in the fields of analytical chemistry, nanomaterials and biomedical engineering.